INFLUENCE OF SHORT-TERM HYPERTHERMIA ON RELICT PLANTS GINKGO L. AND MAGNOLIA L. - NUZHYNA, N.; HOLUBENKO, A.; PALAGECHA, R.; FUTORNA, O.; GENZERSKA, N.; GAIDARZHY, M. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
In connection with global climatic changes, which are accompanied by sharp temperature fluctuations, it is important to study the heat resistance of relict plants in order to improve the understanding of the mechanisms of adaptation and survival of organisms in these conditions. Identification of rare and useful plant species more resistant to high temperatures will make it possible to recommend them for use in landscaping, agriculture, medicine, and the like. The work was carried out on magnolias and ginkgo, since these plants are not only important for landscape design all over the world, but are also valued for the content of biologically active substances that are used in medicine and agriculture. Plants of Ginkgo biloba L., Magnolia obovata Thunb., Magnolia kobus DC. and Magnolia denudata Desr. warmed up for three hours at + 40 ° C, the control group was at + 26 ° C. The stress response was analyzed for the level of lipid peroxidation, superoxide dismutase and peroxidase activity, as well as the content of flavonoids and photosynthetic pigments in the studied plants. The photosynthesizing system of all studied species did not undergo any damaging effects due to the action of hyperthermia. Ginkgo biloba plants have shown very high resistance to high temperatures and stability of the antioxidant and pigment systems. Representatives of all the species of magnolia that we have considered can be positioned in the direction of decreasing resistance to sudden increases in temperature: Magnolia kobus → Magnolia obovata → Magnolia denudata. A higher resistance to hyperthermia was found in plants native to Japan. M. denudata was the least resistant species, possibly due to insufficient activity of antioxidant enzymes.